Understanding MAT access in the context of unused MAT capacity in the United States: when increasing rural MAT capacity is not enough - Carolyn Carpenedo Mun; Rachel Zambrano; Eileen Tallman; Heather Schuler; Elena Bresani; Kathleen Meyers (Substance Abuse Treatment, Prevention, and Policy)
Abstract Background Section 1262 Consolidated Appropriations Act of 2023 eliminates the federal DATA waiver registration requirement to prescribe buprenorphine for opioid use disorder (OUD), along with patient limits, perhaps as a way to increase provider capacity to prescribe buprenorphine. Understanding the factors that influence provider capacity, patient access, and whether community need for MAT is met could inform how to capitalize on DATA waiver eliminations in the United States. Methods This observational study utilized required reporting from two cohorts of the Rural Communities Opioid Response Program (RCORP). Consortia (N = 80) provided data on OUD/SUD-related services, service area information, consortium membership, and grant progress, including barriers to and facilitators of achievements. These data were combined with National Survey of Drug Use and Health (NSDUH) and U.S. Census Bureau’s 2016−2020 American Community Survey (ACS) 5-Year Estimates Data to examine MAT capacity, access, and service area need. Results A 79% increase in potential buprenorphine prescribers from 2019 to 2022 resulted in 1,060 rural providers with the ability to prescribe buprenorphine. The number of individuals who received MAT increased by 42% over the same three years, with over 20,000 individuals receiving MAT by the end of the funding period. While both capacity and access did increase, an additional 11,454 individuals could have potentially received buprenorphine if all waivered providers prescribed to a conservative patient limit of thirty patients. 70% of consortia provided MAT to at least 11.5% of their estimated service area need (national rate of MAT provision among individuals 18 years and older with an OUD), indicating unused MAT capacity was not related to lack of service area need. Provider (e.g., concerns of clinical complexity), patient (e.g., mistrust of the healthcare system), pharmacy (e.g., cost concerns), and pharmacist (e.g., stigma) barriers impacted MAT provision and availability. Conclusion MAT treatment capacity is a necessary but not exclusive requirement for increasing access to MAT. Addressing the multi-faceted barriers to prescribing MAT, particularly buprenorphine, will be critical to ensure the Consolidated Appropriations Act of 2023 does in fact result in a larger workforce that actually prescribes buprenorphine and a pharmacy system that stocks these medications.